ANALYSIS STUDY OF THE MOVEMENT OF THE INDONESIAN WOMEN'S ULAMA CONGRESS (KUPI) IN AGAINST SEXUAL VIOLENCE AND CHILD MARRIAGE - Hidayatulloh, Taufik; Syifa, Bahro (Universitas Islam Negeri Raden Intan Lampung, 2022)
Society's stigma regarding the role of women in the erroneous interpretation of religious texts makes women a creature that occupies the second position after men. The discriminatory interpretation of religious texts has limited the scope for women. One movement that pays attention to women's issues is the Indonesian Women's Ulema Congress (KUPI). KUPI formulates issues such as sexual violence, child marriage, and environmental damage. This research examines two issues, namely fighting sexual violence and child marriage with an analytical study of the movement of the Indonesian Women's Ulama Congress. This type of qualitative research uses descriptive-analytical and descriptive-interpretive methods, describing and explaining the consequences of sexual violence and child marriage. The results of this study indicate that sexual violence and child marriage are not at all good for anyone, instead they are bad. Therefore, these two things must receive serious attention from various parties in prevention efforts.